A critical legal history of French banking and industrialisation: an alternative to the law and development framework. Issue 2 (12th December 2019) - Moudud, Jamee K
Abstract: Money is central to production and the constitutional theory of money has emphasised its fundamentally public foundations, with flows of credit being demand-determined. Using France as a case study, this paper challenges the Law and Development framework by discussing law's constitutive role in promoting industrialisation via the mobilisation of credit.